2020
DOI: 10.1002/ptr.6722
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer molecular mechanisms of oleocanthal

Abstract: Cancer is among the leading causes of mortality worldwide. Current cancer therapies are associated with serious side effects, which further damage patients' health. Therefore, the search for new anticancer agents with no toxic effects on normal and healthy cells is of great interest. Recently, we and other groups have demonstrated that oleocanthal (OLC), a phenolic compound from extra virgin olive oil, exhibits antitumor activity in various tumor models. However, the underlying mechanisms and intracellular tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 151 publications
0
16
0
Order By: Relevance
“…The OLE-linked pungent sensation seems to be mediated via the activation of transient receptor potential cation channel subtype A1 (TRPA1), which is known to mediate neurogenic and chronic inflammation [ 15 ]. Nevertheless, OLE is getting more scientific attention due to its interesting biological activities, most antioxidant, anti-inflammatory, antimicrobial, anticancer and neuroprotective effects [ 13 , 16 ] , even though it makes up only 10% of the olive’s polyphenols (0.2 mg/kg up to 498 mg/kg) influenced by several different factors such as geographical location, olive fruit maturity, agricultural techniques, oil extraction and storage conditions, or even cooking procedures [ 16 ]. It is noteworthy that diet consumption of 25–50 mL EVOO provides around 10 mg of OLE daily, corresponding to near 10% of ordinary ibuprofen dose [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The OLE-linked pungent sensation seems to be mediated via the activation of transient receptor potential cation channel subtype A1 (TRPA1), which is known to mediate neurogenic and chronic inflammation [ 15 ]. Nevertheless, OLE is getting more scientific attention due to its interesting biological activities, most antioxidant, anti-inflammatory, antimicrobial, anticancer and neuroprotective effects [ 13 , 16 ] , even though it makes up only 10% of the olive’s polyphenols (0.2 mg/kg up to 498 mg/kg) influenced by several different factors such as geographical location, olive fruit maturity, agricultural techniques, oil extraction and storage conditions, or even cooking procedures [ 16 ]. It is noteworthy that diet consumption of 25–50 mL EVOO provides around 10 mg of OLE daily, corresponding to near 10% of ordinary ibuprofen dose [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… Control of cell proliferation. Phenolic compounds, such as oleocanthal, are able to act on the expression of genes that control the proliferation, apoptosis, and differentiation of cancer cells [ 13 , 33 , 34 , 133 ]. There is in vitro evidence showing that polyphenols in EVOO alter microRNAs in cancer cells, while hydroxytyrosol appears to exert strong antiproliferative effects in human colon adenocarcinoma cells [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest in this clinical population are the possible effects of oleic acid on satiety and oral tolerance to oleic acid-based formulas. In clinical trials with healthy volunteers, oleic acid ingestion was shown to induce greater postprandial satiety [ 132 ] by increasing levels of the endocannabinoid oleylethanolamide, which was associated with a reduced caloric intake at the next meal [ 133 ]. However, this satiating capacity may be lost in overweight or obese individuals, due to a reduced hormonal and motor response to oleic acid intake because of their higher BMI and habitual dietary fat intake [ 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used an OC enriched EVO oil extract (OCF), in which the OC represents 55.1% of the total content. The OC concentration in the EVO oils is variable, ranging from 0.2 mg/kg to 498 mg/kg [ 41 ], depending on several factors, such as the cultivar and the production techniques [ 42 ], and it represents about 10% of the total phenolic compounds in the EVO oil [ 43 , 44 ]. The data regarding the OC bioavailability are very few, even if the OC metabolites have been found in human urine [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%